Laboratory-Based Evaluation of Anemia in Young Adults Using CBC and Serum Ferritin - Aljabri, Nawaf Khalid; Sharif, Mohammed Ahmed; Alzahrani, Ahmed Saeed Saleh; Abualsaud, Danya Ahmed; Alghamdi, Alya Saud Ali; Alghamdi, Abdullah Saad Guzai; Hakami, Ahmed Habeeb; Almoqbil, Talal Abdullah Saleh; Alsewaihy, Aziz Jumaan; Almuntashiri, Ahmed Abdullah Ahmed; Alkinani, Ahmed Ali; Alkhebary, Jalal (Journal of Ecohumanism, 2024)
Anemia in young adults is a significant yet often underdiagnosed condition that can profoundly affect physiological function, cognitive development, academic performance, work productivity, and overall quality of life. Laboratory evaluation forms the cornerstone of diagnosing anemia, enabling not only the detection but also the classification of its diverse etiologies. The Complete Blood Count (CBC) provides a comprehensive assessment of red blood cell indices, hemoglobin concentration, and related hematologic parameters, offering vital clues into the type and severity of anemia. Serum ferritin measurement complements CBC findings by reflecting the body's iron stores and helping differentiate iron deficiency anemia from other microcytic or normocytic anemias. Accurate diagnosis, however, requires more than technical measurement; it demands a nuanced understanding of laboratory data in the context of the patient's clinical status. This detailed review synthesizes the perspectives of Laboratory Specialists, Senior Laboratory Scientists, Microbiology Molecular Specialists, Medical Laboratory Officers, Technicians, and Medical Technologists, illustrating how multidisciplinary collaboration optimizes the diagnostic workflow. Critical attention is given to pre-analytical, analytical, and post-analytical variables, quality assurance protocols, molecular diagnostic advancements, and emerging technologies that are reshaping the laboratory landscape. By emphasizing a holistic and quality-driven approach, this article aims to enhance diagnostic precision, inform clinical decision-making, and promote improved health outcomes among young adult populations affected by anemia.